THE INFLUENCE OF MOTIVATION AND WORK DISCIPLINE ON THE PERFORMANCE OF OUTSOURCING EMPLOYEES FROM AN ISLAMIC PERSPECTIVE (Case Study of Surabaya City Outsourcing Company) - Erwan Aristyanto; Muchlisun Muchlisun (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
This research aims to determine the influence of motivation and work discipline on the performance of PT outsourcing employees. Rajawali Wira Waru. This causal associative research uses a quantitative approach with a research sample of all outsourcing employees who work at PT. RWW was 87 people (saturated sample). The data collection technique used was a questionnaire containing 4 questions relating to the respondent's personal data and 17 questions relating to the variables tested in this research. Data analysis was carried out using multiple regression analysis. The research results indicate that the work motivation variable has a positive and significant effect on employee performance variables by 26.5%; work discipline variables have a positive and significant influence on employee performance variables by 32%; and work motivation variables and work discipline variables simultaneously have a positive and significant influence on employee performance variables of 38.2%.